Classic Fairy Tales : Cinderella - Alligator Books Limited (Alligator Books Limited, 2006)
A long time ago there lived a gentleman and his charming wife, who took great pride in raisingtheir only daughter to be a good and well behaved girl. The child was most obedient and loved her parents dearly. Sadly, after along illness, the little girl's mother died.
Keywords: Tales / Fairy / Cinderella